2001
DOI: 10.1116/1.1421551
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale patterning using self-assembled polymers for semiconductor applications

Abstract: Thin films of self-organizing diblock copolymers may be suitable for semiconductor applications since they enable patterning of ordered domains with dimensions below photolithographic resolution over wafer-scale areas. We investigate the process window for forming ordered arrays of nanoscale polymer domains in thin films across 8-in.-diam silicon wafers, including the effect of substrate material and surface treatment, annealing conditions, copolymer molecular weight, and film thickness. We also demonstrate pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(145 citation statements)
references
References 15 publications
5
139
1
Order By: Relevance
“…Cylindrical nanodomains have greater aspect ratio features, and have been used to produce dynamic access memory stack capacitors [6][7][8]. In processing these devices, however, Guarini and coworkers showed that the polymer films must be sufficiently thin (<45 nm) to demonstrate a high degree of pore-size uniformity.…”
Section: Nanolithographymentioning
confidence: 99%
“…Cylindrical nanodomains have greater aspect ratio features, and have been used to produce dynamic access memory stack capacitors [6][7][8]. In processing these devices, however, Guarini and coworkers showed that the polymer films must be sufficiently thin (<45 nm) to demonstrate a high degree of pore-size uniformity.…”
Section: Nanolithographymentioning
confidence: 99%
“…First real-world applications of such nanoscale patterning are beginning to be reported; for example, for use in flash memory devices and metal oxide semiconductor (MOS) capacitors. [8][9][10][11] For many potential applications the dimensions of the nanostructures need to be optimized experimentally. Tools to continuously vary the dimensions of the nanopatterns in a predictable and simple manner are required.…”
Section: Introductionmentioning
confidence: 99%
“…After the complete removal of the template, allowing a native SiO x layer to form on the Si, and evaporating a metal, such as Al, a semiconductor capacitor with increased charge storage capacities was produced in a straightforward manner. Guarini et al [39] further investigated the conditions for template generation and showed that CHF 3 could be used as an alternative RIE gas. The hole pattern in silicon was also tone-reversed to form Si 3 N 4 pillars by a three-step process.…”
Section: (A) Ps-b-pi and Ps-b-pbmentioning
confidence: 99%